Peran Kepala Sekolah Sebagai Manajer dalam Meningkatkan Mutu Pendidikan - Mainur Andriya; Chelsi Hestivik; Umi iriani; Syafaruddin (Transformasi Manageria Journal of Islamic Education Management, 2025)
This study aims to analyze the role of school principals as managers in improving the quality of education. Principals serve not only as administrative leaders but also as key drivers in strategically designing, implementing, and evaluating school programs. This research employs a literature review method with a descriptive qualitative approach by analyzing various relevant sources, academic journals, and previous research findings. The results show that principals who perform their managerial roles effectively can create a conducive learning environment and enhance the quality of both academic and non-academic learning. In practice, principals must empower teachers, facilitate student development, and establish strong communication with parents and the community. However, several challenges arise, including low student motivation, limited teacher availability, and lack of parental support. Therefore, school principals are required to demonstrate adaptive, solution-oriented, and collaborative leadership to overcome these obstacles and support the optimal achievement of educational goals.